Strategi Social Media Marketing Melalui Dukungan Teknologi Informasi dalam Kajian Kualitatif Pada UMKM Kota Bandung - Budi Harto; Panji Pramuditha; Arief Yanto Rukmana; Harnavela Sofyan; Hana Rengganawati; Andina Dwijayanti; Teti Sumarni (Program Studi Hubungan Masyarakat Politeknik LP3I, 2023)
This qualitative study explores the development of a technology-enabled social media marketing strategy for MSMEs (Micro, Small and Medium Enterprises) in Bandung City. Through analyzing how MSMEs in Bandung City utilize social media and technology in their marketing efforts, as well as identifying the benefits gained and challenges faced so far. In this research method, we surveyed a number of MSMEs in Bandung and conducted structured interviews with them. The implementation of social media marketing strategies, their impact on business performance, and the factors that influence the implementation of these strategies are described through qualitative analysis of the collected data. The results of this study show that most MSMEs in Bandung City have adopted social media marketing strategies using various technological tools. The study also identified significant benefits obtained by MSMEs, such as increased online visibility, increased interaction with customers, increased sales, and increased content creativity..